Izid rehabilitacije rekreativnih športnikov po poškodbi kolena - Marn-Vukadinović, Duša (Rehabilitacija (Ljubljana), 2016)
Background: Soft tissue knee injury is one of the most prevalent impairments treated at the outpatient rehabilitation clinic of the University Rehabilitation Institute in Ljubljana. Our rehabilitation program is aimed at improving knee muscle strength, neuromuscular control and walking capacity. A prospective study was designed to find out if our rehabilitation program has an important impact on these parameters. Methods: The study included 53 recreational athletes after operative or conservative surgical treatment of the unilateral knee ligament and/or meniscal and/or chondral or muscular injury. At the end of the first phase of the rehabilitation program isokinetic dynamometric measurements of both knee muscles strength was performed. Walking capability was assessed with the Oxford Knee Status (OKS) questionnaire. The same procedure was repeated at the end of the rehabilitation program. Descriptive statistics were calculated for the dynamometric parameters and OKS score, and the absolute and relative improvement of the knee muscle strength was analysed using Wilcoxon%s test. Results: Muscle strength of the injured knee and the OKS scores statistically significantly improved after the rehabilitation. Conclusion: Recreational athletes who had suffered unilateral soft tissue knee injury can expect improvement of knee muscle strength and perceived level of activity after the rehabilitation program comprising neuromuscular training and strengthening.
Keywords: isokinetic dynamometry; izokinetična dinamometrija; Knee; koleno; Oxford Knee Status; Oxfordska kolenska lestvica; rehabilitacija; Rehabilitation; sport injury; športne poškodbe; vocational rehabilitation